Facing diseases caused by trypanosomatid parasites: rational design of multifunctional oxidovanadium(IV) complexes with bioactive ligands - Scalese, Gonzalo; Machado, Ignacio; Salazar, Fabiana; Coitiño, E. Laura; Correia, Isabel; Pessoa, João Costa; Pérez-Díaz, Leticia; Gambino, Dinorah (Frontiers in Chemical Biology, 2024)
Searching for new prospective drugs against Chagas disease (American trypanosomiasis) and Leishmaniasis, a series of five heteroleptic vanadium compounds, [V IV O(L-H)(mpo)], where L are 8-hydroxyquinoline derivatives and mpo is 2-mercaptopyridine N-oxide, are synthesized and characterized. Comprehensive characterizations are conducted in solid state and in solution. The compounds are evaluated on epimastigotes and trypomastigotes of Trypanosoma cruzi and in promastigotes of Leishmania infantum, alongside on VERO cells, as a mammalian cell model. The compounds exhibit activity against both forms of T. cruzi and promastigotes of L. infantum, with the trypomastigote infective stage of T. cruzi displaying the highest sensitivity. The most selective vanadium compound [V IV O(L2-H)(mpo)], with L2 = 5-chloro-7-iodo-8-hydroxyquinoline, globally shows adequate selectivity towards the parasite and was selected to carry out further indepth biological studies. [V IV O(L2-H)(mpo)] significantly impacted the infection potential of cellderived trypomastigotes and hindered the replication of the T. cruzi amastigote form. Low total vanadium uptake by T. cruzi parasites and preferential accumulation in the soluble proteins fraction, with negligible localization in the DNA fraction, are determined. A trypanocide effect is observed across various concentrations of the compound. The generation of oxidative stress and the induction of mitochondria-dependent apoptosis are proposed as the main mechanisms of the parasite's death by the V IV O compounds. Both theoretical predictions and experimental data support the hypothesis that inhibiting the parasite-specific enzyme NADH-fumarate reductase activity plays a crucial role in the trypanocidal action of these complexes. Globally, [V IV O(L-H)(mpo)] complexes could be considered interesting anti-T. cruzi agents that deserve further research.